KONSTRUKSI PENDIDIKAN ISLAM TRANSFORMATIF DALAM MAJLIS DZIKIR MANAQIB DI MADRASAH BERBASIS PESANTREN - Ramadhan, Riski; Anam, Nurul (International Conference on Humanity Education and Society (ICHES), 2024)
The weakness of religious and moral character in students at this time is one of the complex problems. As many students do not understand the ethics of respect for teachers, elders, or colleagues. This study aims to determine the construction of transformative Islamic education in the spiritual aspects, behavior, and knowledge of students through the activities of the Manaqib dzikir majlis. The method used in this study uses a qualitative approach with descriptive methods, and the data was obtained through observation, interviews, and documentation. The results showed that the majlis dhikr manaqib activity was the right activity to cultivate religious character, affected the breadth of students' knowledge, and formed student morale.